THE IMPLEMENTATION OF TRANSLANGUAGING IN ENGLISH LANGUAGE LEARNING VIDEO - Firly Nuryogawati (Journal of English Language Teaching and Literature (JELTL), 2023)
English is one of the foreign languages that can be useful for people who connect to share information beyond the media, including in the education sector. Furthermore, many Indonesians try to educate themselves in this language with some media flexibility, dominantly from domestic media. In several media, translanguaging has existed in the bilingual learning English language, strictly Indonesian. In this study, the researcher captured translanguaging implementation in the instructor's explanation in the English learning video on one YouTube channel and classified them according to Iversen's theory (2019). The researcher used a qualitative approach that used the content analysis method and thematic data analysis to observe and describe certainly translanguaging implementation on the three English learning videos on the GIA Academy YouTube channel. According to the report, the application of translanguaging in the English learning videos evaluated is that the teacher utilises translanguaging approaches that vary according to demands. Translanguaging is utilized in three English learning videos to explain each brief visual of the information in the form of PowerPoint to explain the subchapter, which is highly complicated learning content. The researcher also provided feedback on the English Teaching Language in Indonesia’s social platform.